Pengaruh Kualitas Produk dan Harga Terhadap Keputusan Konsumen Brayen Snack Kediri - Primadani, Desy Eka; Ruhamak, Muhammad; Juwarni, Dwi (Universitas Kadiri, 2023)
This study aims to determine the effect of product quality and price on purchasing decisions of Brayen Snack Kediri. The research method used is descriptive and verification method with a total sample of 100 respondents. Testing research instruments using validity and reliability tests. The data analysis method used is multiple linear regression analysis, multiple correlation and coefficient of determination. The results of the study show that there is a positive and significant influence between product quality and price on purchasing decisions. The magnitude of the influence of product quality and sales promotion on purchasing decisions for the Product Quality variable is 0.01 <0.05 and the t-count value is 3.505 <the t-table value is 1.984, for the Price variable is 0.000 <0.05 and the t-count value is 5,135 > t-value table 1.984 and the effect of price and quality is 0.000 <0.05 and the calculated f value is 157.372 > the f table value is 3.15. So it can be concluded that price and quality have an influence on the purchasing decision variable.